Laminate, manufacturing method of laminate, and deinking method of laminate

By forming a structure of a high acid acrylate compound anchor layer and ink layer on the substrate, combined with alkaline solution treatment, the problem of separation between active energy line cured ink coating and substrate is solved, and the material recycling efficiency and environmental friendliness are improved.

JP7626161B2Active Publication Date: 2025-02-04TOYO INK MFG CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2023066273
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-04-14
Publication Date
2025-02-04
Estimated Expiration
2043-04-14

Smart Images

  • Figure 0007626161000001
    Figure 0007626161000001
  • Figure 0007626161000002
    Figure 0007626161000002
  • Figure 0007626161000003
    Figure 0007626161000003
Patent Text Reader

Abstract

To provide a laminate that has superior physical properties as the laminate, including scratch resistance, and also has superior deinking properties for recycling a substrate with an ink layer composed of active energy ray-curable ink, and a method for producing the laminate.SOLUTION: A laminate comprises an anchor layer and an ink layer on a substrate, in this order. The anchor layer is a layer formed by curing an active energy ray-curable anchor agent comprising a (meth) acrylate compound with an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less, as a (meth) acrylate compound, with an active energy ray. The ink layer is a layer formed by curing an active energy ray-curable ink with an active energy ray.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate, a method for manufacturing a laminate, and a method for deinking a laminate. [Background technology]

[0002] Compared to oxidative polymerization, penetration drying, and hot air drying oil-based inks and varnishes, active energy ray curing inks and varnishes are convenient in that they cure instantly, have the ability to form a strong cured film, and are non-VOC (non-petroleum-based volatile organic compounds), so they are widely used in the package printing industry for applications ranging from beverage and food packaging, pharmaceutical packaging, and cosmetic packaging, to general paper containers.

[0003] In the food packaging field in particular, the ideal form of active energy ray curable ink / varnish would be electron beam (hereafter also referred to as "EB") curable ink, which does not contain photopolymerization initiators and takes into consideration safety and security for humans and the environment; however, due to the large initial capital investment required, it is difficult to say that this is common, and ultraviolet ray (hereafter also referred to as "UV") curable ink is more prevalent on the market.

[0004] In recent years, it is known that there has been a gradual shift to LED curing systems that use UV-LED light sources that are energy-saving and suppress the generation of ozone and heat, energy-saving UV systems that use a single metal halide lamp that eliminates the infrared range that generates heat and the ultraviolet range that generates ozone, and energy-saving UV systems that reduce the number of UV lamps from the usual 3 to 4 to just 1.

[0005] Energy-saving UV-curable inks and varnishes designed to accommodate these new systems have recently been increasingly replaced by ordinary oil-based inks and varnishes, especially in commercial printing, and are required to have the same performance as ordinary oil-based inks and varnishes, including printability and print quality. An increasing number of inks are being certified as "recyclable UV-curable inks" with a rank A certification for recyclability. However, not all UV systems on the market will be replaced by energy-saving UV systems, and many still use conventional UV systems (many of which are rated B in recyclability). UV-curable inks and varnishes are generally considered to be more difficult to recycle than general oil-based inks and varnishes, except for recyclable energy-saving UV-curable inks and some recyclable UV-curable inks. In order to simplify recycling when collecting printed materials, it is considered to be extremely difficult and nearly impossible to separate printed materials that are printed with non-recyclable UV-curable or other active energy ray-curable inks and varnishes.

[0006] Similarly, there is an urgent need to develop methods to make it easier to recycle substrates, even if they are not paper. This is because in recent years, UV curing devices, UV-LED curing devices, and EB curing devices that are less susceptible to heat have been developed, and even if the substrate is thin, it is now possible to irradiate it with active energy rays without causing thermal damage, resulting in an increase in the use of active energy ray-curable inks and varnishes.

[0007] In particular, measures against marine pollution are required as part of global environmental measures for plastic substrates, and there is an urgent need to develop a plastic recovery system that does not allow microplastics, which cause marine pollution, to flow into the ocean. Compared to chemical recycling, which chemically decomposes and reuses materials such as plastics, material recycling, which pelletizes and reuses materials, is easier and more convenient. However, if the active energy ray-curable ink / varnish is not removed from the substrate, the remaining ink / varnish will get into the melting process of the substrate, making it difficult for the substrate to return to its original color, and there is a high possibility that the uses of the recycled substrate will be limited. Therefore, the development of a simple method to remove additives such as active energy ray-curable ink / varnish and adhesives from packaging materials such as plastics will lead to an increase in the efficiency of material recycling.

[0008] Furthermore, if it becomes possible to easily remove active energy ray-curable inks and varnishes from a wide range of substrates, including not only soft packaging materials but also synthetic paper, rigid plastic substrates such as PET bottle caps, nonwoven fabrics and metals, and thereby easily reuse the substrate materials, it will be possible to reduce the use of fossil resources by improving recycling efficiency, and ultimately contribute to a reduction in carbon dioxide emissions.

[0009] For example, Patent Document 1 discloses an organic solvent-based ink for a release layer that can be removed by alkali treatment, a laminate such as a printed matter that includes a release layer using this ink, and a method for recycling this laminate. However, the ink that can be removed is limited to ink that uses a solvent, and there is no simple deinking method for active energy ray-curable ink, which is generally considered to be solvent-free.

[0010] For example, Patent Document 2 discloses a deinking method using an anchor agent for a release layer that can be removed by alkali treatment, but the anchor is limited to one that uses a rosin-modified resin.

[0011] For this reason, when using general active energy ray-curable inks, which are expected to become more widespread, and in particular at least one ink selected from the group consisting of active energy ray-curable offset printing inks, active energy ray-curable flexographic printing inks, and active energy ray-curable resin letterpress printing inks, which have excellent film strength and are considered to be difficult to deink, it is desirable to establish a printed matter that has excellent deinking suitability, and a method for producing such a printed matter. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] JP 2020-090627 A [Patent Document 2] Patent No. 7078189 Summary of the Invention [Problem to be solved by the invention]

[0013] The object of the present invention is to provide a laminate which has excellent physical properties as a laminate, such as scratch resistance, and which has excellent deinking properties in the recycling process of a substrate having an ink layer made of an active energy ray-curable ink, and a method for producing said laminate, as well as to provide a deinking method for said laminate. [Means for solving the problem]

[0014] Means for Solving the Problems The present inventors conducted extensive research to solve the above problems and, as a result, discovered that the above problems can be solved by the laminate and the method for producing the laminate described below, thereby completing the present invention.

[0015] That is, the present invention provides a laminate having an anchor layer and an ink layer in this order on a substrate, the anchor layer is a layer obtained by curing an active energy ray-curable anchor agent containing a (meth)acrylate compound with active energy rays, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, The ink layer is a volatile organic compound (VOC) Active energy ray curable offset printing ink that does not contain volatile organic compounds (VOC) Active energy ray curable flexographic printing ink that does not contain volatile organic compounds and (VOC) The present invention relates to a laminate comprising a layer formed by curing, with active energy rays, at least one ink selected from active energy ray-curable resin letterpress printing inks not containing

[0016] The present invention also relates to the above laminate, which further comprises a varnish layer on the ink layer.

[0018] The present invention also provides a method for producing a laminate, comprising the steps of: A step 1 of applying an active energy ray-curable anchor agent containing a (meth)acrylate compound onto a substrate and curing the agent with active energy rays to obtain a laminate having an anchor layer on the substrate; A volatile organic compound is added to the anchor layer of the laminate having the anchor layer on the substrate. (VOC) Active energy ray curable offset printing ink that does not contain volatile organic compounds (VOC) Active energy ray curable flexographic printing ink that does not contain volatile organic compounds and (VOC) a step 2 of printing at least one ink selected from active energy ray-curable resin letterpress printing inks not containing Including, The present invention relates to a method for producing a laminate, wherein the (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less.

[0019] The present invention also relates to a method for producing the above laminate, which further includes a step 3 of printing an active energy ray-curable varnish on the ink layer of the laminate having an anchor layer and an ink layer on the substrate, and curing the varnish with active energy rays to obtain a laminate having a varnish layer on the ink layer.

[0021] The present invention also provides a method for deinking a laminate having an anchor layer and an ink layer in this order on a substrate, the method comprising the steps of: the anchor layer is a layer obtained by curing an active energy ray-curable anchor agent containing a (meth)acrylate compound with active energy rays, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, The ink layer is a volatile organic compound (VOC) Active energy ray curable offset printing ink that does not contain volatile organic compounds (VOC) Active energy ray curable flexographic printing ink that does not contain volatile organic compounds and (VOC) a layer obtained by curing, with active energy rays, at least one ink selected from active energy ray-curable resin letterpress printing inks not containing The present invention relates to a method for deinking a laminate, in which the laminate is stirred in an alkaline aqueous solution, the anchor layer is dissolved in the alkaline aqueous solution, and the ink layer is deinked from the substrate.

[0022] The present invention also provides a method for deinking a laminate having an anchor layer, an ink layer, and a varnish layer on a substrate in this order, comprising the steps of: the anchor layer is a layer obtained by curing an active energy ray-curable anchor agent containing a (meth)acrylate compound with active energy rays, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, The ink layer is a volatile organic compound (VOC) Active energy ray curable offset printing ink that does not contain volatile organic compounds (VOC) Active energy ray curable flexographic printing ink that does not contain volatile organic compounds and (VOC) a layer obtained by curing, with active energy rays, at least one ink selected from active energy ray-curable resin letterpress printing inks not containing The varnish layer is a layer obtained by curing an active energy ray-curable varnish with active energy rays, The present invention relates to a method for deinking a laminate, in which the laminate is stirred in an alkaline aqueous solution, the anchor layer is dissolved in the alkaline aqueous solution, and the ink layer is deinked from the substrate. Effect of the Invention

[0024] The present invention has made it possible to provide a laminate that has excellent physical properties as a laminate, such as scratch resistance, and also has excellent deinking properties in the recycling process of a substrate having an ink layer made of an active energy ray-curable ink, and a manufacturing method for said laminate, as well as a deinking method for said laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below. Note that the present invention is not limited to the following embodiments, and can be practiced with various modifications within the scope of the spirit of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0026] One embodiment of the present invention is a laminate having an anchor layer and an ink layer in this order on a substrate, in which the anchor layer is a layer obtained by curing, with active energy rays, an active energy ray-curable anchor agent containing, as a (meth)acrylate compound, a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less, and the ink layer is a layer obtained by curing, with active energy rays, an active energy ray-curable ink.

[0027] Moreover, one embodiment of the present invention is a laminate having an anchor layer and a varnish layer in this order on a substrate (excluding the case where an ink layer of active energy ray-curable ink cured by active energy rays is included between the anchor layer and the varnish layer), in which the anchor layer is a layer of active energy ray-curable anchor agent containing a (meth)acrylate compound having an acid value of 20 mg KOH / g or more and 500 mg KOH / g or less cured by active energy rays, and the varnish layer is a layer of active energy ray-curable varnish cured by active energy rays.

[0028] <Ink layer> <Active energy ray curable ink> The active energy ray-curable ink (hereinafter, also referred to as "ink") used in the ink layer of the present invention is characterized by containing a colorant and a (meth)acrylate compound.

[0029] [Coloring agent] In the present invention, the ink contains a colorant. As the colorant, at least one of a pigment and a dye can be used. From the viewpoint of light resistance, a pigment is preferred. The pigment that can be used in the present invention is not particularly limited, and any known pigment can be used. The pigment can be either an inorganic pigment or an organic pigment.

[0030] Examples of inorganic pigments include carbon blacks such as furnace black, lamp black, acetylene black, and channel black, iron oxide, and titanium oxide.

[0031] Examples of organic pigments include soluble azo pigments such as β-naphthol, β-oxynaphthoic acid, β-oxynaphthoic acid anilide, acetoacetate anilide, and pyrazolone; Examples of the pigments include insoluble azo pigments such as β-naphthol, β-oxynaphthoic acid anilide, acetoacetate anilide monoazo, acetoacetate anilide disazo, and pyrazolone; phthalocyanine pigments such as copper phthalocyanine blue, halogenated (e.g., chlorinated or brominated) copper phthalocyanine blue, sulfonated copper phthalocyanine blue, and metal-free phthalocyanine; and polycyclic pigments and heterocyclic pigments such as quinacridone, dioxazine, threne (pyranthrone, anthranthrone, indanthrone, anthrapyrimidine, flavanthrone, thioindigo, anthraquinone, perinone, perylene, etc.), isoindolinone, metal complex, quinophthalone, and diketopyrrolopyrrole.

[0032] More specifically, in terms of the CI color index, black pigments include CI Pigment Black 1, 6, 7, 9, 10, 11, 28, 26, 31, and the like.

[0033] Examples of white pigments include CI Pigment White 5, 6, 7, 12, and 28.

[0034] Examples of yellow pigments include CI Pigment Yellow 1, 2, 3, 12, 13, 14, 16, 17, 18, 24, 73, 74, 75, 83, 93, 95, 97, 98, 100, 108, 109, 110, 114, 120, 128, 129, 138, 139, 174, 150, 151, 154, 155, 167, 174, 176, 180, 185, and 213.

[0035] Blue or cyan pigments include CI Pigment Blue 1, 2, 14, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and the like.

[0036] Red or crimson pigments include CI Pigment RED 1, 3, 5, 19, 21, 22, 31, 38, 42, 43, 48:1, 48:2, 48:3, 48:4, 48:5, 49:1, 50, 52, 53:1, 57:1, 57:2, 58:4, 63:1, 81, 81:1, 81:2, 81:3, 81:4, 83, 90, 104, 108, 11 2, 114, 122, 144, 146, 148, 149, 150, 166, 168, 169, 170, 172, 173, 176, 177, 178, 184, 185, 187, 193, 202, 209, 214, 242, 254, 255, 264, 266, 269, CI Pigment Violet 19, etc.

[0037] Green pigments include CI Pigment Green 1, 2, 3, 4, 7, 8, 10, 15, 17, 26, 36, 45, 50, and the like.

[0038] Purple pigments include CI Pigment Violet 1, 2, 3, 4, 5:1, 12, 13, 15, 16, 17, 19, 23, 25, 29, 31, 32, 36, 37, 39, and 42. Orange pigments include CI Pigment Orange 13, 16, 20, 34, 36, 38, 39, 43, 51, 61, 63, 64, 74, and the like.

[0039] In the present invention, the above pigments may be used alone or in combination of two or more.

[0040] In the present invention, the pigment can be used in any content as long as the desired concentration can be reproduced on the surface of the printing substrate, and the content is preferably 5 to 30 mass % and more preferably 10 to 25 mass % based on the total amount of the ink.

[0041] [(Meth)acrylate compounds] In this specification, unless otherwise specified, "(meth)acryloyl", "(meth)acrylic acid", "(meth)acrylate", and "(meth)acryloyloxy" respectively mean "acryloyl and / or methacryloyl", "acrylic acid and / or methacrylic acid", "acrylate and / or methacrylate", and "acryloyloxy and / or methacryloyloxy". In addition, "PO" stands for "propylene oxide" and "EO" stands for "ethylene oxide". In addition, X in EO-modified (X) and PO-modified (X) represents the number of moles of EO and PO modified, and Y in polyethylene glycol (Y) di(meth)acrylate represents the approximate molecular weight of the polyethylene glycol portion.

[0042] The active energy ray-curable ink of the present invention contains a (meth)acrylate compound. The (meth)acrylate compound that can be used in the active energy ray-curable ink is not particularly limited as long as it is a compound having one or more (meth)acryloyl groups, and includes any form of monomer, oligomer, or polymer. Here, the term "monomer" refers to a compound that is the minimum structural unit for constituting an oligomer or a polymer, and the term "oligomer" refers to a polymer having structural units based on 2 to 100 monomers.

[0043] Specific examples of the (meth)acrylate compound used in the present invention include the compounds shown below.

[0044] [(Meth)acrylate compounds] (monomer) 2-Ethylhexyl (meth)acrylate, 2-Hydroxyethyl (meth)acrylate, 2-Hydroxypropyl (meth)acrylate, β-Carboxylethyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, tetrahydrofurfuryl acrylate, alkoxylated tetrahydrofurfuryl acrylate, caprolactone (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isoamyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, isodecyl (meth)acrylate, 3,3,5-trimethylcyclohexanol (meth)acrylate ) acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (oxyethyl) (meth)acrylate, 1,4-cyclohexanedimethanol (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, benzyl (meth)acrylate, EO-modified (2) nonylphenol acrylate, 2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl acrylate, and other monofunctional (meth)acrylate monomers having one (meth)acryloyl group in the molecule; 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol (200) di(meth)acrylate, polyethylene glycol (300) di(meth)acrylate, polyethylene glycol (400) di(meth)acrylate, polyethylene glycol (600) di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate , dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, EO-modified (2) 1,6-hexanediol di(meth)acrylate, PO-modified (2) neopentyl glycol di(meth)acrylate, (neopentyl glycol-modified) trimethylolpropane di(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, EO-modified (4) bisphenol A di(meth)acrylate, PO-modified (4) bisphenol A di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, dicyclopentanyl di(meth)acrylate, and other bifunctional (meth)acrylate monomers having two (meth)acryloyl groups in the molecule; Trimethylolpropane tri(meth)acrylate, EO modified (3) trimethylolpropane tri(meth)acrylate, EO modified (6) trimethylolpropane tri(meth)acrylate, PO modified (3) trimethylolpropane tri(meth)acrylate, trifunctional (meth)acrylate monomers having three (meth)acryloyl groups in the molecule, such as pentaerythritol tri(meth)acrylate, Pentaerythritol tetra(meth)acrylate, EO-modified (4) pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and other tetrafunctional (meth)acrylate monomers having four acryloyl groups in the molecule; Pentafunctional (meth)acrylate monomers having five (meth)acryloyl groups in the molecule, such as dipentaerythritol penta(meth)acrylate; and hexafunctional (meth)acrylate monomers having six (meth)acryloyl groups in the molecule, such as dipentaerythritol hexa(meth)acrylate.

[0045] (Oligomer) Examples of the oligomer include urethane acrylate oligomers such as aliphatic urethane acrylate oligomers and aromatic urethane acrylate oligomers, acrylic ester oligomers, polyester acrylate oligomers, and epoxy acrylate oligomers having 1 to 6 (meth)acryloyl groups.

[0046] [Other ingredients] In the present invention, the ink may contain, if necessary, in addition to the above-mentioned components, a polymerization initiator, an amine compound, a resin, a polymerization inhibitor, a surface tension adjuster, a wax, an extender pigment, a pigment dispersant, an antifoaming agent, an ultraviolet absorber, an antioxidant, an antistatic agent, and the like.

[0047] (Polymerization initiator) In the present invention, the ink may contain a polymerization initiator. The polymerization initiator preferably contains a polymerizable initiator for radical or cationic polymerization, and more preferably contains a photopolymerization initiator. The polymerization initiator in the present invention is a compound that undergoes a chemical change through the action of light or through interaction with the electronically excited state of the sensitizing dye to generate radicals or cations, and among these, a photoradical polymerization initiator is preferable from the viewpoint of being able to initiate polymerization by exposure to light.

[0048] In the present invention, the photo-radical polymerization initiator is not particularly limited, and known ones can be used. Specific examples include benzophenone compounds, dialkoxyacetophenone compounds, α-hydroxyalkylphenone compounds, α-aminoalkylphenone compounds, acylphosphine oxide compounds, oxime ester compounds, and thioxanthone compounds. The photo-polymerization initiator may be used alone or in combination of two or more.

[0049] Benzophenone compounds include benzophenone, 2-methylbenzophenone, 3-methylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 4-phenylbenzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(dimethylamino)benzophenone, [4-(methylphenylthio)phenyl]-phenylmethanone, 2-chloro-4-phenyl-benzophenone, 1-{4-[(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylbenzenesulfonyl)propan-1-one, and polybutylene glycol bis(4-benzoylphenoxy)acetate.

[0050] Examples of the dialkoxyacetophenone compounds include 2,2-dimethoxy-2-phenylacetophenone, dimethoxyacetophenone, and diethoxyacetophenone.

[0051] The α-hydroxyalkylphenone compounds include 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxymethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, oligo[2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone], 2,3-dihydro-6-(2-hydroxy-2-methyl-1-oxopropyl)-1,1,3-trimethyl-3-[4-(2-hydroxy-2-methyl- 2-hydroxy-1-[4-[4-(2-hydroxy-2-methyl-1-oxopropyl)phenyl]-1H-indene and 2,3-dihydro-5-(2-hydroxy-2-methyl-1-oxopropyl)-1,1,3-trimethyl-3-[4-(2-hydroxy-2-methyl-1-oxopropyl)phenyl]-1H-indene mixture, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methylpropynyl)benzyl]phenyl]-2-methylpropan-1-one, 2-hydroxy-1-[4-[4-(2-hydroxy-2-methylpropanoyl)phenoxy]phenyl]-2-methylpropan-1-one, 1-[4-(1,1-dimethylethyl)phenyl]-2-hydroxy-2-methylpropan-1-one, and the like.

[0052] Examples of α-aminoalkylphenone compounds include 2-methyl-1-[4-(methoxythio)-phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 1,2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, and 1-(9,9-dibutyl-9H-fluoren-2-yl)-2-methyl-2-morpholinopropan-1-one. phospho-4-yl-propan-1-one, polyethylene glycol di(β-4-[4-(2-dimethylamino-2-benzyl)butanonylphenyl]piperazine)propionate, 2-benzyl-2-dimethylamino-1-(4-piperidinylphenyl)-1-butanone, 1-(biphenyl-4-yl)-2-methyl-2-morpholinopropan-1-one, 1-(biphenyl-4-yl)-2-methoxy-2-morpholinopropan-1-one, and the like.

[0053] Examples of the acylphosphine oxide compound include diphenylacylphenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, tris(phenyl(2,4,6-trimethylbenzoyl)phosphinic acid) polyethylene glycol ester, ethyl(2,4,6-trimethylbenzoyl)phenylphosphineate, and bis(2,4,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide.

[0054] The oxime ester compounds include 1-[4-(phenylthio)phenyl]octane-1,2-dione, 2-benzoyl oxime, ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyl oxime), 3-cyclopentyl-1-(4-(phenylthio)phenyl)propane-1,2-dione-2-(o-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H -carbazol-3-yl]-3-cyclopentylpropane-1-(o-acetyloxime), methanone, [8-[[(acetyloxy)imino][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methyl]-11-(2-ethylhexyl)-11H-benzo[a]carbazol-5-yl]-, (2,4,6-trimethylphenyl), 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, and the like.

[0055] Examples of thioxanthone compounds include 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propylthioxanthone, 2-chlorothioxanthone, poly(oxy-1,4-butanediyl), α-[2-[(9-oxo-9H-thioxanthenyl)oxy]acetyl]-ω-[[2-[(9-oxo-9H-thioxanthenyl)oxy]acetyl]oxy]-, 1,3-di({α-[1-chloro-9-oxo-9H-thioxanthen-4-yl]oxy}acetylpoly[oxy(1-methylethylene)])oxy]-2,2-bis({α-[1-chloro-9-oxo-9H-thioxanthen-4-yl]oxy}acetylpoly[oxy(1-methylethylene)])oxymethyl)propane, and the like.

[0056] The content of the photopolymerization initiator is preferably from 1 to 20% by mass, and more preferably from 5 to 15% by mass, based on the total amount of the ink.

[0057] (Amine compounds) In the present invention, the ink may contain an amine compound. There is no particular limitation on the amine compound, and any known amine compound can be used. By using the amine compound as a component of the active energy ray-curable ink, it is expected that the effect of the hydrogen abstraction type photopolymerization initiator can be enhanced. Specific examples include N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, ethyl 4-(dimethylamino)benzoate, N,N-dihydroxyethylaniline, triethylamine and N,N-dimethylhexylamine, poly(oxy-1,2-ethanediyl,α-[4-(dimethylamino)benzoyl]-ω-[[4-(dimethylamino)benzoyl]oxy]-, bis-N,N-[2-(4-dimethylaminobenzoyl)oxyethylene-1-yl ]methylamine, poly(oxy-1,2-ethanediyl), α-[4-(dimethylamino)benzoyl]-ω-[[4-(dimethylamino)benzoyl]oxy]-, poly[oxy(methyl-1,2-ethanediyl), α-[4-(dimethylamino)benzoyl-ω-butoxy-, 2-butoxyethyl-4-(dimethylamino)benzoate, 2-(dimethylamino)ethyl benzoate, etc. The amine compounds may be used alone or in combination of two or more kinds.

[0058] (resin) In the present invention, the ink may contain a resin, which reduces the cure shrinkage of the coating film that occurs during curing, suppresses curling of the substrate, and improves adhesion to the anchoring agent.

[0059] The resins may be used alone or in combination of two or more kinds. The content of the resin is preferably 1 to 20% by mass based on the total mass of the ink.

[0060] Specific examples of the resin include polyvinyl chloride, (meth)acrylic resin, styrene (meth)acrylic resin, epoxy resin, polyester resin, polyurethane resin, cellulose derivatives (e.g., ethyl cellulose, cellulose acetate, nitrocellulose), vinyl chloride-vinyl acetate copolymer, polyamide resin, polyvinyl acetal resin, diallyl phthalate resin, alkyd resin, rosin-modified alkyd resin, petroleum resin, urea resin, synthetic rubber such as butadiene-acrylonitrile copolymer, etc. Among these, diallyl phthalate resin and polyester resin are more preferable from the viewpoint of dispersibility.

[0061] (Polymerization inhibitor) In the present invention, the ink may contain a polymerization inhibitor, specific examples of which include 4-methoxyphenol, hydroquinone, methylhydroquinone, t-butylhydroquinone, 2,6-di-t-butyl-4-methylphenol, phenothiazine, and aluminum salt of N-nitrosophenylhydroxylamine.

[0062] The content of the polymerization inhibitor is preferably 0.01 to 2% by mass relative to the total mass of the ink, from the viewpoint of increasing the stability of the ink while maintaining the curability.

[0063] (wax) In the present invention, the ink may contain wax. By containing wax, it is possible to improve the abrasion resistance, scratch resistance, blocking prevention, smoothness, and scratch prevention. There is no particular limitation on the wax, and any known wax can be used. For example, natural wax and synthetic wax can be used. Examples of natural waxes include carnauba wax, Japan wax, lanolin, montan wax, paraffin wax, and microcrystalline wax. Examples of synthetic waxes include Fischer-Tropsch wax, polyethylene wax, polypropylene wax, and polytetrafluoroethylene wax.

[0064] The content of the wax is preferably 0.1 to 5% by mass based on the total mass of the ink.

[0065] (Extender pigment) In the present invention, the ink may contain an extender pigment, such as clay, talc, barium sulfate, calcium carbonate, ground calcium carbonate, barium carbonate, magnesium carbonate, silica, or bentonite.

[0066] (Pigment dispersant) In the present invention, the ink preferably contains a pigment dispersant in order to improve the pigment dispersibility. There is no particular limitation on the pigment dispersant, and any known pigment dispersant can be used. Among them, a resin-type pigment dispersant having a basic functional group is preferable, and examples of the basic functional group include a primary, secondary, or tertiary amino group, and nitrogen-containing heterocycles such as pyridine, pyrimidine, and pyrazine. Further, as the skeleton constituting the resin-type pigment dispersant, a fatty acid amine skeleton and / or a urethane skeleton are more preferable since good pigment dispersibility can be easily obtained.

[0067] Examples of the pigment dispersant include the Ajisper series (Ajisper PB821, PB822, PB824, etc.) manufactured by Ajinomoto Fine-Techno Co., Ltd., the Solsperse series (Solsperse 00, Solsperse 32000, Solsperse 38500, etc.) manufactured by Lubrizol, and the Disperbyk series (BYK-162, BYK-168, BYK-183, etc.) manufactured by BYK-Chemie.

[0068] The content of the pigment dispersant is preferably from 0.1 to 10% by mass, and more preferably from 0.2 to 5% by mass, based on the total mass of the ink.

[0069] The active energy ray curable ink in the present application is preferably at least one ink selected from active energy ray curable offset printing ink, active energy ray curable flexographic printing ink, and active energy ray curable resin letterpress printing ink, because these inks have high film strength and are difficult to deink among active energy ray curable inks, and are inks in which the effects of the present invention are particularly pronounced.

[0070] <Varnish layer> <Active energy ray curable varnish> The active energy ray-curable varnish (hereinafter, also referred to as "varnish") used in the varnish layer of the present invention is characterized by containing a (meth)acrylate compound.

[0071] The materials used in the varnish of the present invention are similar to those in the active energy ray-curable ink described above, except that substantially no colorant is used.

[0072] <Anchor layer> The anchor layer of the laminate of the present invention can be obtained by applying an active energy ray-curable anchor agent containing a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less, and curing it with active energy rays.

[0073] <Active energy ray curable anchoring agent> The active energy ray-curable anchor agent (hereinafter also referred to as "anchor agent") in the present invention contains, as a (meth)acrylate compound, a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less.

[0074] [(Meth)acrylate compounds] The (meth)acrylate compound contained in the anchor agent in the present invention has the same meaning as the (meth)acrylate compound explained in the above-mentioned active energy ray-curable ink.

[0075] [(Meth)acrylate compounds with an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less] The active energy ray-curable anchor agent in the present invention contains, as the (meth)acrylate compound, a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less. By containing a (meth)acrylate compound with an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less, the anchor layer becomes easier to separate (peel off, dissolve, etc.) from the substrate during deinking. The acid value of a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less is preferably 50 to 450 mgKOH / g, more preferably 80 to 400 mgKOH / g, and particularly preferably 100 to 350 mgKOH / g.

[0076] The content of the (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less is preferably 15 to 90 mass%, more preferably 20 to 80 mass%, further preferably 25 to 75 mass%, and particularly preferably 30 to 70 mass%, of the total amount of the active energy ray curable anchor agent. When the content of the (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less is 15 mass% or more, the deinking property is good, and when it is 90 mass% or less, the scratch resistance is good.

[0077] Specific examples of (meth)acrylate compounds having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less include MIRAMER SC6632 and MIRAMER SC6640 manufactured by MIWON Co., Ltd., DPV27 and DPV28 manufactured by Negami Chemical Industrial Co., Ltd., EBECRYL11, (ACA)Z200M, (ACA)Z230AA, (ACA)Z250, (ACA)Z251, (ACA)Z254F, (ACA)Z300, (ACA)Z320, and β-CEA manufactured by Daicel-Allnex Corporation, and 8KQ-2001 and PH-9001 manufactured by Taisei Fine Chemical Co., Ltd.

[0078] [Other ingredients] In the present invention, the anchor agent may contain, if necessary, in addition to the above-mentioned components, silica, alumina, an antifoaming agent, a leveling agent, a tackifier, a preservative, an antibacterial agent, an antirust agent, an adhesion aid, a polymerization initiator, an amine compound, a polymerization inhibitor, wax, an extender pigment, a pigment dispersant, an ultraviolet absorber, an antioxidant, an antistatic agent, and the like.

[0079] (polymerization initiators, amine compounds, extender pigments, pigment dispersants) The polymerization initiator, amine compound, wax, extender pigment, and pigment dispersant that can be contained in the anchor agent in the present invention can be the polymerization initiator, amine compound wax, extender pigment, and pigment dispersant explained in the above-mentioned active energy ray-curable ink, respectively.

[0080] (Polymerization inhibitor) The polymerization inhibitor contained in the anchor agent of the present invention can be added and used by a conventional method. The amount of the polymerization inhibitor is preferably 3% by mass or less, more preferably 0.01 to 1% by mass, based on the total mass of the anchor agent, from the viewpoint of not inhibiting curability.

[0081] Specific examples of polymerization inhibitors that can be used include (alkyl)phenols, hydroquinone, catechol, resorcin, p-methoxyphenol, t-butylcatechol, t-butylhydroquinone, pyrogallol, 1,1-picrylhydrazyl, phenothiazine, p-benzoquinone, nitrosobenzene, 2,5-di-tert-butyl-p-benzoquinone, dithiobenzoyl disulfide, picric acid, cupferron, aluminum N-nitrosophenylhydroxylamine, tri-p-nitrophenylmethyl, N-(3-oxyanilino-1,3-dimethylbutylidene)aniline oxide, dibutyl cresol, cyclohexanone oxime cresol, guaiacol, o-isopropylphenol, butyraldoxime, methyl ethyl ketoxime, and cyclohexanone oxime. In particular, it is preferable to use one or more compounds selected from hindered amines such as 2,2,6,6-tetraalkylpiperidine derivatives, 2,2,6,6-tetramethylpiperidine derivatives, 1-alkyl-2,2,6,6-tetramethylpiperidine derivatives, and 1-hydro-2,2,6,6-tetramethylpiperidine derivatives, which are compounds having two hydrocarbon groups each at the 2-position and the 6-position on the piperidine ring (four in total), and these can inhibit the curing reaction in a printing machine and provide excellent storage stability.

[0082] <Laminate> In one embodiment, the laminate of the present invention is obtained by printing an active energy ray-curable ink on an anchor layer obtained by applying an anchor agent to a substrate and curing the ink with active energy rays, and then curing the ink with active energy rays. In this embodiment, a varnish layer may be further provided on the ink layer. The varnish used for the varnish layer is not particularly limited, and any known varnish can be used, but it is preferable to use an active energy ray-curable varnish or a water-based varnish, and it is particularly preferable to use an active energy ray-curable varnish.

[0083] The method for producing the laminate of this embodiment includes the following steps: A step 1 of applying an active energy ray-curable anchor agent containing a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less to a substrate, and curing the agent with active energy rays to obtain a laminate having an anchor layer on the substrate; A step 2 of printing an active energy ray curable ink on the anchor layer of the laminate having an anchor layer on the substrate, and curing the ink with active energy rays to obtain a laminate having an ink layer on the anchor layer; Includes.

[0084] In addition, the manufacturing method of this embodiment may further include step 3 of printing an active energy ray-curable varnish on the ink layer of a laminate having an anchor layer and an ink layer on the substrate, and curing it with active energy rays to obtain a laminate having a varnish layer on the ink layer.

[0085] In one embodiment, the laminate of the present invention is obtained by printing an active energy ray-curable varnish on an anchor layer obtained by curing an anchor agent applied to a substrate with active energy rays, and curing the varnish with active energy rays.

[0086] The method for producing the laminate of this embodiment includes the following steps: A step 1 of applying an active energy ray-curable anchor agent containing a (meth)acrylate compound having an acid value of 20 mgKOH / g or more and 500 mgKOH / g or less to a substrate, and curing the agent with active energy rays to obtain a laminate having an anchor layer on the substrate; A step 4 of printing an active energy ray curable varnish on the anchor layer of the laminate having an anchor layer on the substrate and curing the varnish with active energy rays to obtain a laminate having a varnish layer on the anchor layer; Includes.

[0087] The substrate is not particularly limited, and known substrates can be used. Specifically, the substrates include polypropylene (PP) (including synthetic paper), polyethylene (PE), polyethylene terephthalate (PET), plastic substrates having inorganic deposition layers such as aluminum, silica, and alumina, aluminum foil, polyvinyl chloride (PVC), polystyrene (PS), nylon, cellophane, metal sheets, and paper (excluding synthetic paper), and are preferably non-absorbent substrates. The substrate may contain various additives such as antistatic agents, antifogging agents, and ultraviolet protection agents.

[0088] In the present invention, the method of printing the active energy ray-curable ink can be a known method, but is preferably used for offset printing using an active energy ray-curable offset printing ink, resin letterpress printing using an active energy ray-curable resin letterpress printing ink, and flexographic printing using an active energy ray-curable flexographic printing ink.

[0089] In the present invention, the method for printing the active energy ray-curable varnish is not particularly limited, and any known method can be used, specifically, a roll coater, gravure coater, flexo coater, air doctor coater, blade coater, air knife coater, squeeze coater, impregnation coater, transfer roll coater, kiss coater, curtain coater, cast coater, spray coater, die coater, offset printing, resin letterpress printing, gravure printing, flexo printing, etc. can be mentioned.

[0090] In the present invention, the method for applying the active energy ray-curable anchor agent is not particularly limited, and any known method can be used.Specific examples of the method include a roll coater, a gravure coater, a flexo coater, an air doctor coater, a blade coater, an air knife coater, a squeeze coater, an impregnation coater, a transfer roll coater, a kiss coater, a curtain coater, a cast coater, a spray coater, a die coater, offset printing, resin letterpress printing, gravure printing, and flexo printing.

[0091] The active energy ray source is not particularly limited and may be any known source, specifically including mercury lamps, xenon lamps, metal hydride lamps, excimer lamps, LEDs (light-emitting diodes) such as ultraviolet light-emitting diodes (UV-LEDs) and ultraviolet laser diodes (UV-LDs), electron beam (EB) irradiation devices, and gas / solid-state lasers.

[0092] <Deinking> In the present invention, deinking is a process for removing ink and varnish components from a printed substrate.

[0093] (Ink component removal process using alkaline aqueous solution) The laminate is, for example, brought into contact with an alkaline aqueous solution in a treatment tank containing the alkaline aqueous solution, thereby removing the ink layer and the varnish layer.

[0094] (Alkaline aqueous solution) In the present invention, the alkaline aqueous solution is an aqueous solution containing an alkaline compound, and the alkaline compound is preferably contained in an amount of 0.5 to 10 mass % of the entire aqueous solution, and more preferably 1 to 5 mass %. The alkaline compound is not particularly limited, but suitable examples include sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2, ammonia, barium hydroxide (Ba(OH)2), sodium carbonate (Na2CO3), etc. Preferred are NaOH and / or KOH.

[0095] (Ink and varnish component removal process) The mechanism by which the ink layer or varnish layer can be detached from the laminate by contacting the above-mentioned alkaline aqueous solution with the laminate is presumed to be that the presence of the above-mentioned resin allows the alkaline aqueous solution to penetrate through the surface of the anchor layer and / or the cross section of the laminate, dissolving the anchor layer. After the anchor layer is applied to the substrate and the ink layer or varnish layer is printed, the laminate that has been made into a packaging container through a bag-making process or the like is preferably cut or crushed in the recycling process or before, so that the laminate comes into contact with the alkaline aqueous solution in a state where the cross section of the laminate is exposed.

[0096] The laminate and the alkaline aqueous solution are preferably contacted while being stirred. The stirring means is not particularly limited, and examples thereof include known stirring equipment such as a general dispersion, radial flow turbine blade, axial flow turbine blade, paddle blade, propeller blade, anchor blade, and high shear mixer. For example, in the case of a 2L flask scale, the stirring rotation speed is preferably 100 to 350 rpm, depending on the shape and size of the stirring blade. The stirring time is preferably 15 minutes or more and 24 hours or less.

[0097] (Base material recovery process) The method for producing recycled substrates of the present invention includes a step of recovering the substrate after the ink layer or varnish layer is removed from the laminate. The step of recovering the substrate refers to a step of separating and recovering the substrate from a treatment tank in which the alkaline aqueous solution, the peeled ink layer or varnish layer fragments, and the substrate are mixed after the laminate is treated with an alkaline aqueous solution, and it is preferable to obtain the substrate with high purity. The method for recovering the substrate is not particularly limited, and for example, separation and recovery based on the size difference between the substrate and the ink layer or varnish layer fragments is preferable, and separation and recovery based on the specific gravity difference is also preferable. Alternatively, separation and recovery can be appropriately performed by a combination of these, but it is preferable to include a separation and recovery step based on the specific gravity difference, and more preferably, a separation and recovery step based on the specific gravity difference and a separation and recovery step based on the size difference are used in combination. In addition, in the separation and recovery process based on the specific gravity difference, it is preferable to recover only the substrate floating in the alkaline aqueous solution in the treatment tank. It is also preferable if impurity components in the alkaline aqueous solution and fragments of the ink layer and varnish layer settle, which makes it easy to separate from the substrate and allows only the substrate to be recovered more accurately. Therefore, the physical properties and transparency of the substrate recycled after recovery are improved. The method of separation based on the specific gravity difference may be a conventionally known method, such as one using a fluidized bed or one using a centrifuge.

[0098] After the ink layer and varnish layer are detached from the laminate and the substrate is recovered, the substrate is washed with water and dried to obtain a recycled substrate. In this case, it is preferable that the recycled substrate is free of any contaminants, including fragments of the detached ink layer and varnish layer, as much as possible. The recycled substrate can be processed into pellets using an extruder or the like and reused as recycled resin. The use of the recycled resin is not limited, and it may be processed into a colorless and transparent film, or may be processed into a molded product with added colorants.

[0099] Available deinking agents include DI-7020, DI-7027, DI-7250, and DI-767 manufactured by Kao Corporation, the DIA-Z series and DIA-Y series manufactured by Nissin Chemical Co., Ltd., and the Riptor series manufactured by Lion Specialty Chemicals. EXAMPLES

[0100] The present invention will be specifically described below with reference to examples and comparative examples. However, the present invention is not limited to the following examples. In the examples and comparative examples, "parts" and "%" represent "parts by mass" and "% by mass", respectively.

[0101] (Anchoring agent 1) 40.0 parts of SC6640, 30.0 parts of SC6632, 22.0 parts of DiTMPTA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC1).

[0102] (Anchoring agent 2) An active energy ray-curable anchoring agent (AC2) was prepared by mixing 80.0 parts of SC6640, 12.0 parts of DPHA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB and stirring using a butterfly mixer.

[0103] (Anchoring agent 3) 15.0 parts of SC6632, 65.0 parts of TMPTA (EO), 12.0 parts of DiTMPTA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC3).

[0104] (Anchoring agent 4) 40.0 parts of SC6632, 40.0 parts of TMPTA (EO), 12.0 parts of DiTMPTA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC4).

[0105] (Anchoring agent 5) 90.0 parts of SC6640, 2.0 parts of TMPTA (EO), 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC5).

[0106] (Anchoring agent 6) 5.0 parts of SC6632, 75.0 parts of TMPTA (EO), 12.0 parts of DiTMPTA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC6).

[0107] (Anchoring agent 7) 70.0 parts of TMPTA (EO), 22.0 parts of DiTMPTA, 5.0 parts of 4MBP, 2.0 parts of TPO, and 1.0 part of EDB were mixed and stirred using a butterfly mixer to prepare an active energy ray-curable anchor agent (AC7).

[0108] <Preparation of Diallyl Phthalate Resin Varnish> 65.0 parts of DPHA, 6.5 parts of TMPTA (EO), and 3.5 parts of DiTMPTA were mixed and heated to 100° C. with stirring. Next, 25.0 parts of diallyl phthalate resin was mixed and dissolved while maintaining the temperature at 100° C. to prepare a diallyl phthalate resin varnish.

[0109] <Ink manufacturing example>

[0110] (Ink manufacturing example 1 (UV ink 1) (active energy ray curable offset printing ink, active energy Ray-curable resin letterpress printing ink 17.0 parts of RAVEN 1080 Ultra, 3.0 parts of BA-2550, 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 1.5 parts of DEABP, 1.5 parts of DETX, 1.0 part of EDB, and 47.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0111] (Ink manufacturing example 2 (UV ink 2) (active energy ray curable offset printing ink, active energy Ray-curable resin letterpress printing ink 17.0 parts of RAVEN 1080 Ultra, 3.0 parts of BA-2550, 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 1.5 parts of DEABP, 1.5 parts of DETX, 1.0 part of EDB, and 47.0 parts of MIRAMER PS-4500 were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0112] (Ink manufacturing example 3 (LED ink) (active energy ray curable ink for offset printing, active energy ray curable ink for resin letterpress printing)) 17.0 parts of RAVEN 1080 Ultra, 3.0 parts of BA-2550, 6.0 parts of TMPTA (EO), 10.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 2.0 parts of TPO, 2.0 parts of DEABP, 2.5 parts of 4MBP, 2.5 parts of DETX, 1.0 part of EDB, and 44.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0113] (Ink Manufacturing Example 4 (UV Flexographic Ink) (Active Energy Ray Curable Flexographic Printing Ink)) 15.0 parts of RAVEN 1080 Ultra, 1.0 part of BA-2550, 16.0 parts of TMPTA (EO), 5.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 2.0 parts of DEABP, 2.5 parts of 4MBP, 2.5 parts of DETX, 1.0 part of EDB, and 6.0 parts of Solsperse 24000 were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink. Then, 39.0 parts of TMPTA (EO) were added and mixed and stirred using a butterfly mixer to prepare an ink.

[0114] (Ink manufacturing example 5 (UV ink yellow) (active energy ray curable offset printing ink, active energy ray curable resin letterpress printing ink)) 15.0 parts of Permanent Yellow BHS, 6.0 parts of TMPTA (EO), 18.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 1.5 parts of DEABP, 1.5 parts of DETX, 1.0 part of EDB, and 47.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0115] (Ink Manufacturing Example 6 (UV Ink Red) (Active Energy Ray Curable Offset Printing Ink, Active Energy Ray Curable Resin Letterpress Printing Ink)) 20.0 parts of Permanent Rubine L5B-01, 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 1.5 parts of DEABP, 1.5 parts of DETX, 1.0 part of EDB, and 47.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare the ink.

[0116] (Ink Manufacturing Example 7 (UV Ink Blue) (Active Energy Ray Curable Offset Printing Ink, Active Energy Ray Curable Resin Letterpress Printing Ink)) 20.0 parts of Heliogen Blue D7088, 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, 3.0 parts of 379, 1.5 parts of DEABP, 1.5 parts of DETX, 1.0 part of EDB, and 47.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0117] (Ink Production Example 9 (EB Ink) (Active Energy Ray Curable Offset Printing Ink, Active Energy Ray Curable Resin Letterpress Printing Ink)) 17.0 parts of RAVEN 1080 Ultra, 3.0 parts of BA-2550, 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, and 54.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0118] <Preparation of oil-based resin varnish> (Example of rosin modified phenolic resin production) In a reaction vessel, 54.3 parts of gum rosin was reacted with 30.8 parts of tertiary butylphenol and 9.4 parts of 92% by weight paraformaldehyde in a xylene solvent under sodium hydroxide catalyst at 100°C for 4 hours, and the phenolic resin from which moisture had been removed was added dropwise at 150°C and reacted for 2 hours. 5.4 parts of glycerin was then added, and the reaction was continued for 15 hours at 250°C using 0.1 parts of calcium oxide as a catalyst. During this time, the mixture was successively removed to obtain a rosin phenolic resin.

[0119] (Example of rosin modified phenolic resin varnish production) Next, 45.0 parts of the rosin-modified phenolic resin as a binder resin, 44.0 parts of soybean oil, 10.0 parts of soybean oil fatty acid normal butyl ester, and 1.0 parts of ALCH were placed in a four-neck flask equipped with a stirrer, a reflux condenser equipped with a water separator, and a thermometer, and heated and stirred at 190°C for 1 hour to obtain a rosin-modified phenolic resin varnish.

[0120] (Ink Manufacturing Example 10 (Oil-based Ink) (Ink other than active energy ray curing ink)) 17.0 parts of RAVEN 1080 Ultra, 3.0 parts of BA-2550, 59.0 parts of rosin-modified phenolic resin varnish, 20.0 parts of soybean oil, 0.5 parts of MK dryer, and 0.5 parts of drying inhibitor CP were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to prepare an ink.

[0121] (Varnish manufacturing example 1 (UV varnish) (Active energy ray curable offset printing varnish, active energy ray curable Chemically-modified resin letterpress varnish 6.0 parts of TMPTA (EO), 13.0 parts of DiTMPTA, 7.0 parts of DPHA, 6.0 parts of 184, 2.0 parts of TPO, 1.0 part of EDB, 3.0 parts of filler, and 62.0 parts of diallyl phthalate resin varnish were mixed and stirred using a butterfly mixer, and then dispersed using a three-roll mill so that the maximum particle size was 7.5 μm or less to produce a varnish.

[0122] The descriptions of the materials used in the examples are as follows: [Coloring agent] ·Permanent Yellow BHS: Manufactured by Clariant, Permanent Yellow BHS (CIPigment Yellow 174) ·Permanent Rubine L5B-01: Manufactured by Clariant, Permanent Rubine L5B-01 (CIPigment Red 57:1) ·HELIOGEN BLUE D7088: Manufactured by BASF, HELIOGEN BLUE D7088(CIPigment Blue 15:3) ·Raven 1080 Ultra: Manufactured by Bilra Carbon, Raven 1080 Ultra Powder (CIPigment Black 7) BA-2550: Morimura Shoji Co., Ltd., alkaline blue toner BA-2550 (CIPigmen t Blue 61) [Extender pigment] Filler: Matsumura Sangyo Co., Ltd., High Filler #5000PJ, talc [(Meth)acrylate compounds] SC6640: MIWON MIRAMER SC6640 (acid value: 255mgKOH / g) SC6632: MIWON MIRAMER SC6632 (acid value: 190mgKOH / g) TMPTA (EO): BASF, LAROMER LR8863, trimethylolpropane ethylene oxide modified triacrylate DiTMPTA: Daicel-Allnex, EBECRYL1142, ditrimethylolpropane tetraacrylate DPHA: MIWON, MIRAMER M600, dipentaerythritol hexaacrylate PS-4500: MIWON, MIRAMER PS-4500, polyester acrylate oligomer [resin] Diallyl phthalate resin: Osaka Soda Co., Ltd., Daiso DAP A [Photopolymerization initiator] 379: IGM RESINS, Omnirad379, 1,2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone TPO: Chemark Chemical Company, CHEMARK TPO, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide DEABP: Chemark Chemical Company, CHEMARK DEABP, 4,4'-bis(dimethylamino)benzophenone 4MBP: Soho Industry Co., Ltd., SB-PI 712 DETX: Chemark Chemical Company, CHEMARK DETX, 2,4-diethylthioxanthone 184: IGM RESINS, Omnirad 184, 1-hydroxy-cyclohexyl phenyl ketone [Amine compounds] EDB: Chemark Chemical Company, CHEMARK EDB, Ethyl 4-(dimethylamino)benzoate [Pigment dispersant] Solsperse24000: Lubrizol, Solsperse24000 [Metal dryer] MK Dryer: Toyo Ink Co., Ltd., MK Dryer [Drying inhibitor] Drying inhibitor CP: Drying inhibitor CP manufactured by Toyo Ink Co., Ltd. [Aluminum gelling agent] ALCH: Manufactured by Kawaken Fine Chemicals Co., Ltd., ALCH, aluminum ethyl acetate diisopropylate [others] Soybean oil fatty acid normal butyl ester: Toshin Yushi Co., Ltd., SFB2 Soybean oil: Nisshin Oillio Group Co., Ltd.: White refined soybean oil

[0123] <Printing anchoring agent onto substrate> In Examples 1 to 12, 14 to 27 and Comparative Examples 2 and 3, an RI tester (a simple printing machine manufactured by Mei Seisakusho Co., Ltd. (a printing machine capable of printing offset printing ink, flexographic printing ink, and resin letterpress printing ink)) was used to print and apply the anchor agent to one side of the substrate described in Table 1 with an ink gauge of 0.25 mL. The coating was then cured with an ultraviolet curing device manufactured by Eye Graphics Co., Ltd. (160 W / cm metal halide lamp) at a conveyor speed of 30 m / min to produce a laminate having an anchor layer on the substrate. In Example 13, a bar coater (No. 4, manufactured by Yasuda Seiki Co., Ltd.) was used to coat the anchor agent shown in Table 1 onto the substrate shown in Table 1. The coating was then cured with an ultraviolet curing device (160 W / cm metal halide lamp) manufactured by Eye Graphics Co., Ltd. at a conveyor speed of 30 m / min to produce a laminate having an anchor layer on the substrate.

[0124] <Ink and varnish printing> In Examples 1 to 22, 24, and Comparative Example 2, the prepared laminate having an anchor layer on a substrate was printed with each sample ink shown in Table 1 using an RI tester with an ink gauge of 0.25 mL, and then the printed matter was cured with an ultraviolet curing device (160 W / cm metal halide lamp) manufactured by iGraphics Co., Ltd. at a conveyor speed of 30 m / min to obtain a laminate having an anchor layer and an ink layer in this order on the substrate. In Example 23, LED ink was printed on the prepared laminate having an anchor layer on a substrate using an RI tester with an ink gauge of 0.25 mL, and the ink was then cured on the printed matter using an ultraviolet curing device (160 W / cm metal halide lamp) manufactured by iGraphics Co., Ltd. at a conveyor speed of 100 m / min to obtain a laminate having an anchor layer and an ink layer in this order on the substrate. In Example 25, EB ink was printed using an RI tester with an ink gauge of 0.25 mL on the prepared laminate having an anchor layer on a substrate, and then the printed matter was irradiated with 30 KGy of electron beams using a low-energy electron beam irradiation device manufactured by ESI Corporation (voltage of 175 KV, nitrogen-substituted atmosphere with an oxygen concentration of 50 ppm) to harden the ink, thereby obtaining a laminate having an anchor layer and an ink layer in that order on the substrate. In Example 26, a laminate having an anchor layer on a substrate was printed with a UV varnish prepared by mixing two parts of UV ink 1 with an ink gauge of 0.25 mL using an RI tester, and the coating was then cured with an ultraviolet curing device (160 W / cm metal halide lamp) manufactured by iGraphics Co., Ltd. at a conveyor speed of 30 m / min to obtain a laminate having an anchor layer and a varnish layer in that order on the substrate. In Example 27, UV ink 1 was printed on the prepared laminate having an anchor layer on a substrate using an RI tester with an ink gauge of 0.25 mL, and the printed matter was cured to form a coating film using an ultraviolet curing device manufactured by iGraphics (160 W / cm metal halide lamp) at a conveyor speed of 30 m / min. Furthermore, UV varnish was printed on the printed matter with an ink gauge of 0.25 mL using an RI tester, and the printed matter was cured to form a coating film using an ultraviolet curing device manufactured by iGraphics (160 W / cm metal halide lamp) at a conveyor speed of 30 m / min. Thus, a laminate having an anchor layer, ink layer, and varnish layer in this order on the substrate was obtained. In addition, in Comparative Example 3, an oil-based ink (an ink other than an active energy ray curable ink) was printed with an ink gauge of 0.25 mL using an RI tester on the prepared laminate having an anchor layer on a substrate, and then the ink was left to harden at room temperature for 24 hours to obtain a laminate having an anchor layer and an ink layer in this order on the substrate. In Comparative Example 1, an oil-based black ink (an ink other than an active energy ray curable ink) was printed directly onto the substrate shown in Table 1 using an RI tester with an ink gauge of 0.25 mL, and then the ink was left to stand at room temperature for 24 hours to cure, thereby obtaining a laminate having an ink layer on the substrate.

[0125] The substrates used in the examples are as follows: PP: Polypropylene sheet manufactured by Okamoto Corporation PE: Taiko FC, manufactured by Futamura Chemical Co., Ltd. PET: Reshine, manufactured by Toyobo Co., Ltd. Aluminum vapor deposition: Gojo Paper Co., Ltd., SPECIALITIES Aluminum foil: Toyo Aluminum Co., Ltd., Leadmax Synthetic paper: New Yupo FGS, manufactured by Yupo Corporation PVC: PVC80C P, manufactured by Lintec Corporation PS: Styrofoam, manufactured by Oishi Sangyo Co., Ltd. Nylon: Made by Unitika Ltd., emblem Cellophane: Futamura Chemical Co., Ltd., PL Metal: ET2.8 tinplate made by Nippon Steel Corporation

[0126] The performance of the obtained laminate was evaluated by the following method, and the results are shown in Table 1.

[0127] <Evaluation of the laminate>

[0128] (Evaluation of scratch resistance) The laminate was evaluated by rubbing the ink surface with cotton cloth. The less rubbing, the better the scratch resistance. The evaluation criteria are as shown below, with ◯, ◯△, and △ being practically preferable. 〇: No rubbing on the printed surface where the ink has been applied 〇△: The ink is rubbed off to the surface of the printed surface. △: The ink is rubbed off to the middle of the printed surface. △×: The ink is rubbed off to the bottom of the printed surface. ×: The coating on the printed surface where the ink was spread disappears

[0129] (Evaluation of Adhesion) The ink side of the laminate was applied with adhesive tape (Nichiban Cellotape (registered trademark) 18 m 1.5m width) is attached and then peeled off vertically at 90 degrees. Base material from Anchor layer The adhesion to the substrate was evaluated based on the ratio of the peeled area. ◯, ◯△, and △ are practically preferable. ○: The anchor layer does not peel off from the substrate. ○△: Peeling of the anchor layer from the substrate is less than 10%. △: Peeling of the anchor layer from the substrate is 10% or more but less than 30%. △×: Peeling of the anchor layer from the substrate is 30% or more but less than 70%. ×: 70% or more of the anchor layer peels off from the substrate

[0130] <Evaluation of deinking ability> The laminates prepared in Examples 1 to 27 and Comparative Examples 1 to 3 were aged at 60° C. for one week, and then stored for an additional 10 days in an environment of room temperature 23±1° C. and humidity 50±2%. Then, they were cut into 30×30 mm pieces, and 90 g of each piece was used as a sample for testing.

[0131] <Evaluation of deinking properties of laminate> In a 2L flask, 1.5L of 30°C hot water, 11mL of 3.75% sodium hydroxide solution, and 11mL of deinking agent (DI-7027 manufactured by Kao Corporation) diluted to 1.5% were added, and the sample was then added and stirred at 300 rpm for 20 minutes. Two minutes after the start of stirring, the sample adhering to the lid was washed away into the tank with a small amount of water. After the desorption was completed, the substrate was removed and the extent to which the area of ​​each 30 x 30 mm was covered with ink was visually evaluated. ○: Ink has come off from 95% or more of the substrate △: Ink has come off from 90% to less than 95% of the substrate ×: Ink has come off from less than 90% of the substrate

[0132] Products that are rated as ◯, ◯△, or △ in the three evaluations of scratch resistance, adhesion, and deinking ability are considered to be practical.

[0133] From the above, it has been found that the easily deinkable laminate of the present invention has deinking properties while providing the print quality required in the market, such as scratch resistance and adhesion.

[0134] [Table 1]

[0135] [Table 1]

[0136] [Table 1]

[0137]

Table 1

Claims

1. A laminate having an anchor layer and an ink layer in this order on a substrate, the anchor layer is a layer obtained by curing an active energy ray-curable anchor agent containing a (meth)acrylate compound with active energy rays, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, the content of the (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less is 5 to 40 mass% based on the total amount of the active energy ray-curable anchor agent, A laminate, in which the ink layer is a layer obtained by curing, with active energy rays, at least one type of ink selected from an active energy ray-curable offset printing ink containing no volatile organic compounds (VOCs) and an active energy ray-curable resin letterpress printing ink containing no volatile organic compounds (VOCs) (excluding the case where the (meth)acrylate compound in the anchor agent contains urethane acrylate).

2. A laminate as described in claim 1, except when the substrate is a shrink plastic substrate.

3. A method for producing a laminate, comprising the steps of: A step 1 of applying an active energy ray-curable anchoring agent containing a (meth)acrylate compound onto a substrate and curing the agent with active energy rays to obtain a laminate having an anchor layer on the substrate; a step 2 of printing at least one ink selected from an active energy ray-curable offset printing ink containing no volatile organic compounds (VOCs) and an active energy ray-curable resin letterpress printing ink containing no volatile organic compounds (VOCs) on the anchor layer of the laminate having an anchor layer on the substrate, and curing the ink with active energy rays to obtain a laminate having an ink layer on the anchor layer; Including, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, and the content of the (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less is 5 to 40 mass % in the total amount of the active energy ray-curable anchor agent (excluding the case where the (meth)acrylate compound in the anchor agent contains a urethane acrylate).

4. A method for producing a laminate as described in claim 3, except when the substrate is a shrink plastic substrate.

5. A method for deinking a laminate having an anchor layer and an ink layer on a substrate in this order, comprising the steps of: the anchor layer is a layer obtained by curing an active energy ray-curable anchor agent containing a (meth)acrylate compound with active energy rays, The (meth)acrylate compound contains a (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less, the content of the (meth)acrylate compound having an acid value of 80 mgKOH / g or more and 500 mgKOH / g or less is 5 to 40 mass% based on the total amount of the active energy ray-curable anchor agent, the ink layer is a layer obtained by curing at least one ink selected from an active energy ray-curable offset printing ink containing no volatile organic compounds (VOCs) and an active energy ray-curable resin letterpress printing ink containing no volatile organic compounds (VOCs) with active energy rays; A method for deinking a laminate, in which the laminate is stirred in an alkaline aqueous solution, the anchor layer is dissolved in the alkaline aqueous solution, and the ink layer is deinked from the substrate (excluding the case where the (meth)acrylate compound in the anchor agent contains a urethane acrylate).

6. A method for deinking a laminate as described in claim 5, except when the substrate is a shrink plastic substrate.

Citation Information

Patent Citations

  • UV (ultraviolet) curing ink and application thereof

    CN103232754A

  • Recycle type peeling sheet and manufacture therefor

    JP1993269932A

  • Thermoplastic resin product having print thereon and method of printing on thermoplastic product

    JP1996034867A

  • Radiation curing type ink composition

    JP1999246811A

  • Latent hydrophilic resin and composition containing the resin

    JP2001261746A